A comparison of ground and treadmill energy cost of race walkers - Bosquet, L.; Gayda, M.; Pap, F.; Leger, L. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
A prerequisite in the development of a multistage field test is the knowledge of the energy cost of the specific mode of locomotion. There are only few data available about race walking, and most of them have been measured on a treadmill. Therefore, the aim of this study was to compare ground and treadmill energy cost of race walking with the purpose of determining the incrementation rate of a specific multistage field test. Methods: Six highly trained race walkers of national to international calibre gave their written informed consent to participate in the study. They completed two randomly ordered sessions separated by at least 24 h, one on a 200 m indoor synthetic track, one a laboratory motorized treadmill. The protocol consisted in walking with proper technique at 8, 10, 12 and 14 km.h-1 for 4 minutes without rest in between. Thereafter, speed was incremented by 0.5 km.h-1 every minute until exhaustion to determine peak oxygen consumption. Oxygen uptake and related gas exchange measures were determined continuously on a 30 s basis using an automated cardiopulmonary exercise system (K4b2, Cosmed, Italy). Results: Mean was 64.5 ± 10.3 ml.min-1.kg-1 and was reached at 14.7 ± 0.8 km.h-1. Combining data of all participants resulted in almost identical -speed relationships between track (y = 4.90x - 7.10, R2 = 0.53) and treadmill race walking (y = 4.85x - 6.74, R2 = 0.72). There was a high interindividual variability, as evidenced by a large standard error of estimate (SEE; 9.3 and 7.6 ml.min-1.kg-1 for track and treadmill race walking, respectively), and by the ~ 30 ml.min-1.kg-1 difference between less and more economical race walkers at 14 km.h-1. Interestingly, we observed a significant relationship between economy of walking at 14 km.h-1 and (r = 0.68, p<0.05). In this small sample of athletes, less economical race walkers compensated their lack of efficiency by higher . The visual inspection of individual curves confirmed the validity of using a linear model. The average energy cost of race walking estimated from such a model increased by 5 ml.min-1.kg-1 per km.h-1, either on the track or the treadmill. In comparison, the average energy cost of running is 3.5 ml.min-1.kg-1per km h-1. (X1 in ml kg-1 min-1) and walking economy (X2, at 14 km h-1 during the track test in ml kg-1 min-1) explained 92% of the variability of the maximal speed attained during the treadmill test (Y = 15.089 + 0.073 X1 - 0.07862 X2, R2 = 0.84 SEE = 0.39 km h-1). Conclusion: Despite a high interindividual variability, our results underscore the usefulness of developing a specific multistage field test for race walking. Considering that optimal incrementation should allow an increase in of ~ 3.5 ml.min-1.kg-1 every two minutes, a speed incrementation of 0.5 to 0.75 km.h-1 every two minutes appears to be more specific to race walking than the 1 km.h-1 every two minutes incrementation that is usually used in running.